2021
DOI: 10.3390/medicina57030224
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism in Children and Adolescents with Down Syndrome: A Comprehensive Review

Abstract: The role of bruxism in children and adolescents with Down syndrome, the most often diagnosed congenital syndrome, is still unclear. Therefore, this study aims to conduct a narrative review of the literature about bruxism in children and adolescents with Down syndrome to identify the prevalence, risk factors, and possible treatments of this disorder. Although an accurate estimate of its prevalence could not be inferred, it appears that bruxism is more prevalent in Down syndrome individuals rather than in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
18

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
1
5
0
18
Order By: Relevance
“…Según este último consenso, al bruxismo no debe considerarse como un trastorno sino más bien como un factor de riesgo o un factor protector para la salud buco dental, lo que coincide con los estudios de Luconi et al (2021) y Lobbezoo et al (2018), ya que manifiestan que el bruxismo no se debe considerar como una patología, sino que puede presentarse en personas con trastornos del comportamiento de movimientos oculares rápidos, apnea obstructiva del sueño, epilepsia, y demás afecciones que requieren atención multidisciplinaria (Luconi et al, 2021) (Lobbezoo et al, 2018). Según la literatura, puede ser un factor de riesgo cuando el paciente presente trastornos temporomandibulares preexistentes o simultáneos, desgaste mecánico de piezas dentales, etc.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Según este último consenso, al bruxismo no debe considerarse como un trastorno sino más bien como un factor de riesgo o un factor protector para la salud buco dental, lo que coincide con los estudios de Luconi et al (2021) y Lobbezoo et al (2018), ya que manifiestan que el bruxismo no se debe considerar como una patología, sino que puede presentarse en personas con trastornos del comportamiento de movimientos oculares rápidos, apnea obstructiva del sueño, epilepsia, y demás afecciones que requieren atención multidisciplinaria (Luconi et al, 2021) (Lobbezoo et al, 2018). Según la literatura, puede ser un factor de riesgo cuando el paciente presente trastornos temporomandibulares preexistentes o simultáneos, desgaste mecánico de piezas dentales, etc.…”
Section: Discussionunclassified
“…Además, se han relacionado como causa del bruxismo a diversos factores como: psicosociales, obstrucción de la vía aérea, hábitos parafuncionales, la calidad del sueño, enfermedades sistémicas, uso de pantalla con fines recreativos, consumo de azúcar agregado y medicamentos (Calvano Küchler et al, 2020;Chisini et al, 2020;Goettems et al, 2017;Luconi et al, 2021;Restrepo, Santamaría, et al, 2021;Vieira et al, 2020).…”
Section: Etiologíaunclassified
See 2 more Smart Citations
“…Therefore, this study aimed to evaluate whether children with Down syndrome are more affected by malocclusion or not. According to Luconi et al, there is no correlation between malocclusion and bruxism, which proves that there is no biological significance between the conditions, and hence, malocclusion does not increase the probability of bruxism among children with Down syndrome [15]. Based on the previously published systematic review, findings indicated that malocclusion was more prevalent among children suffering from Down syndrome; therefore, orthodontic treatment needs are also higher among children suffering from Down syndrome.…”
Section: Discussionmentioning
confidence: 99%